Geomorphologic units of the Middle São Francisco River alluvial plain, Northeastern Brazil - Santos, Landerlei Almeida [UNESP]; Latrubesse, Edgardo Manuel (Revista Brasileira de Geomorfologia, 2022)
The Sao Francisco rivers is the largest river draining the cratonic areas of Cerrado savanas and semiarid Caatinga environments in NE Brazil. This study presents the first geomorphologic map of the Middle Sao Francisco River, and describe the main morphosedimentary units of the alluvial plain. The use of high-resolution satellite images, digital elevation models, cores data from previous studies, and morphosedimentary field descriptions were the procedures applied. The morphological composition indicates that the alluvial plain is a mosaic of morphosedimentary units. Eight geomorphological units were recognized. The unit classified as Impeded Floodplain is the richest in terms of diversity of geomorphological features, and was sub-classify in seven morphosedimentary subunits. At least three fluvial stages must be responsible for building the current mosaic of morphologies displayed on the floodplain. It is likely that a braided channel is the oldest type of system that operated in the region and left marks on the preserved floodplain. Subsequently, an important wetter stage induced a change in the behavior of the main river to a multichannel type, responsible for the main features observed current. Finally, the current, drier stage, with lower river flow, has controlled the development of the bank accretion floodplain and fluvial-aeolian floodplain during the Late Holocene. Therefore, these paleohidrological variations of the São Francisco River must play a key role in the construction of the complex and floodplain relic of the Middle São Francisco River.
Unidades geomorfológicas da planície aluvial do Médio Rio São Francisco, Nordeste do Brasil
Keywords: Alluvial plain; Geomorphology; Middle São Francisco River